0490 A randomised control crossover trial of a theory based intervention to improve sun-safe and healthy behaviours in construction workers: study protocol. (21st August 2017) - Nioi, Amanda; Wendelboe-Nelson, Charlotte; Cherrie, John
Abstract : Exposure to sunlight can have both positive and negative health impacts. Excessive exposure to ultra-violet (UV) radiation from the sun can cause skin cancer, however, insufficient exposure to sunlight has a detrimental effect on the production of Vitamin D. In the construction industry there are already proactive behaviours for safety onsite, but sun-safety and health remains a low priority. There is limited research in understanding the barriers to adopting sun-safe behaviours and the association this may have with Vitamin D production. This paper reports the study protocol for a text messaging (SMS) and supportive smartphone app intervention, which aims to reduced UV exposure and promote appropriate dietary changes to boost Vitamin D intake. Approximately 60 adult construction workers will be recruited across Scotland and southern England. Randomisation to the intervention will occur at site level and participants will receive both the control (no text service) and intervention (daily text message and supportive app). The intervention messages will be delivered daily to participant's smartphone; they will also be sent a link to download the supportive app. There will be three waves of data collection across the year, each study epoch lasting 21 days (intervention messages sent on workdays only). The primary outcome measure is Vitamin D level (using blood spot sampling) this will be taken at the start and end of each 21 day cycle (control and intervention). This study will provide important information about the effectiveness of a technology-based intervention to promote sun-safe and healthy behaviours amongst outdoor construction workers.